1998
DOI: 10.1177/0011128798044003003
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Dispositions and Domestic Violence Recidivism

Abstract: The effects of court dispositions on rearrest for domestic violence was examined for a sample of adults arrested for misdemeanor domestic violence in Hamilton County (Cincinnati), Ohio. Arrestees were tracked for one year after their sentences, if any, had been served. Qualitatively, more severe sentences (e.g., jail combined with probation versus either probation or jail) corresponded with lower recidivism likelihoods. Also, these sentences appeared most effective for persons with greater stakes in conformity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 11 publications
0
43
0
Order By: Relevance
“…Electronic monitoring, for example, is one useful tool for supervising domestic abusers (Erez & Ibarra, 2007). Other studies noted success of intensive supervision programs tied with multiple sanctions (Thistlethwaite, Wooldredge, and Gibbs, 1998). These strategies have direct bearing on offenders' self-control levels; they provide formal mechanisms that make sure that decision making by offenders can be monitored and controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic monitoring, for example, is one useful tool for supervising domestic abusers (Erez & Ibarra, 2007). Other studies noted success of intensive supervision programs tied with multiple sanctions (Thistlethwaite, Wooldredge, and Gibbs, 1998). These strategies have direct bearing on offenders' self-control levels; they provide formal mechanisms that make sure that decision making by offenders can be monitored and controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies address misdemeanor charges of domestic violence (Thistlethwaite, Wooldredge, and Gibbs, 1998;Ventura and Davis, 2005), another deals with drunk driving (Taxman and Piquero, 1998), and two are concerned with the "conviction" of juveniles for serious offenses (Fagan, Kupchik, and Liberman, 2003;Hagan and Palloni, 1990). To our knowledge, no research to date has examined the labeling effect of a felony conviction for adults, which is the focus of the current study.…”
Section: Conviction Effects Researchmentioning
confidence: 99%
“…Moreover, Dalton (2001) found that perception of threat (e.g., consequences from the legal system) had no effect on program completion. However, there is some research that suggests that those who have a higher stake in conformity are less likely to recidivate (Sherman et al, 1992 andThistlewaite et al, 1998).…”
Section: Factors Related To Domestic Violence Perpetration Treatmentmentioning
confidence: 99%